The influence of principal leadership, work competence, and work motivation on the performance of elementary school teachers in Yogyakarta - Setyaningrum, Desi; Irambona, Alfred (Indonesian Journal of Educational Management and Leadership, 2024)
Purpose − The purpose of this study is to examine the impact of principal leadership, work competence, and work motivation on the performance of elementary school teachers in the Kotagede sub-district. Method − The research uses a descriptive correlational approach with a quantitative method and involves a sample of 54 teachers. Data is collected through questionnaires, and analysis includes descriptive analysis as well as prerequisite tests such as normality, linearity, and multicollinearity. Hypothesis testing is conducted using multiple regression analysis. Findings − The results indicate a positive and significant influence of principal leadership, teacher competence, and teacher motivation on the performance of elementary school teachers in the Kotagede Subdistrict Yogyakarta, with an F value of 4.117 and a significance value of 0.000, which is less than 0.05. Therefore, in order to enhance the performance of public elementary school teachers in the Kotagede sub-district, attention to factors such as principal leadership, work competence, and teacher motivation is essential.